Immunodeficiency Disorders in Congenital Heart Diseases (Review) - Elena A. Degtyareva; Bupe M. Mwela; Andrey P. Prodeus; Dmitry Yu. Ovsyannikov; Marina G. Kantemirova; Olga V. Alekseeva; Dmitry A. Kudlay; Alexey I. Kim; Inessa E. Nefedova; Tatiana V. Rogova; Margarita R. Tumanyan; Ilya A. Korsunskiy (Union of pediatricians of Russia, 2023)
The study data of the last two decades on primary and secondary immunodeficiency in congenital heart defects (CHD) as a cause of frequent infectious complications before and after cardiac surgery are presented. Based on screenings of various levels, data are provided on the greater severity of immunological disorders in critical and cyanotic CHD in conotruncal defects compared with those in septal defects and stenotic defects. Violations were more often related to T-cell function and immunoglobulin deficiency (especially the IgG and IgG4 subgroups). Various types of primary immunodeficiency were found in 13 genetic syndromes in combination with CHD. The review discusses the possibility of using the technique of quantitative determination of DNA TREC and KREC - by-products of maturation of T- and B-cell receptors, which allows us to judge the defects of the T- and B-cell links of the immune system to predict infectious complications in children with CHD. The data of our own study of 200 infants with CHD (in 5% of cases with syndromic forms of CHD) are presented, where a decrease in TREC was found in 23.5% of cases, including all infants with syndromic forms, more often with cyanotic and conotruncal CHD and in children admitted in critical conditions. In children with reduced TREC values, infectious complications in the postoperative period were observed significantly more often than in children with normal indicators (36 and 3.6%, respectively). The analysis of publications confirmed the importance of TREC and KREC screening for targeted preoperative preparation in order to reduce postoperative complications and reduce the risk of mortality in CHD.